Analisis Penerapan Akuntansi Pertanggung Jawaban Biaya Dalam Menilai Kinerja Manajer Pusat Biaya Pada Kantor Kebun Sei Baruhur PTPN III - Rizah Ummammy; Arnida Wahyuni Lubis; Hendra Harmain (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
Accountability accounting is a way of keeping track of money that is used to plan, measure, and evaluate the success of an organization based on the responsibilities and authority of its managers. The role of the financial system in keeping track of spending. Managers' success is measured by how well and efficiently they worked to reach the organization's goals. Companies need to make a plan in order to organize a cost centre manager performance improvement activity. The goal of this study is to find out how cost responsibility accounting is used at Kantor Kebun Sei Baruhur PTPN III to judge the success of cost center managers. A qualitative descriptive method is used in this study. Based on the results of this study, Kantor Kebun Sei Baruhur PTPN III has been able to successfully use responsibility accounting to evaluate the work of the cost center manager. A budget was used as the basis for reducing costs, which led to this good planning. Even though there are differences between what was planned and what was paid, some are good and some are not. Kantor Kebun Sei Baruhur PTPN III has shown that it is an official and useful tool for judging how well cost center managers do their jobs